Gut microbiome and fecal metabolite profiles in obese school-aged children from Northern Thailand - Therdtatha, Phatthanaphong; Gruneck, Lucsame; Nachalam, Poramet; Jinatham, Vasana; Saninjuk, Kritsakorn; Nakayama, Jiro; Popluechai, Siam (Frontiers in Microbiology, 2025)
Although the gut microbiota of school-aged children has been extensively studied, there is a significant lack of knowledge regarding the relationship between fecal metabolite profiles and the gut microbiota in the context of obesity in young children, particularly in Thailand. To elucidate this association, we analyzed fecal gut microbiota and metabolites of 67 school-aged children across various body mass index (BMI) and categorized: normal (n = 30), overweight (n = 20), and obese (n = 17), employing next-generation sequencing (NGS) and ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-QTOF/MS), respectively. Obese children exhibited distinct profiles of both gut microbiota and metabolites compared to N and OW children. Genera enriched in the OB group included Faecalibacterium, Collinsella, Megamonas, Brevundimonas, and Phascolarctobacterium. Nearly 80 percent of distinct negative-ion features were more abundant in the higher BMI groups. Multivariate analyses revealed that BMI had a stronger influence on variations in fecal metabolite profiles than on gut microbiota composition. Shifts in association patterns between the gut microbiota and predicted microbial functions (KOs) were observed across BMI groups. Although no direct associations were observed between gut microbiota and metabolites, microbiome–metabolite interactions were predominantly mediated through microbial functions. Our findings highlight non-targeted metabolites associated with high BMI in school-aged children and illustrate microbiome–metabolite crosstalk through a microbe–function–metabolite triangle, which may be mediated through functional pathways rather than direct taxon–metabolite correlations.